1995
DOI: 10.1088/0953-8984/7/17/016
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance investigations of MgSiF6.6H2O:Mn2+single crystals

Abstract: EPR studies were performed on MgSiFs . 6Hz0 single crystals using MnZt paramagnetic probes substituted for Mg2+ ions. The spin-Hamiltonian parameters (SHPS) are determined accurately for the different phases: the monoclinic phase below T, = 301 K, the rhombohedral phase above To = 370 K and the intermediate phase between T, and To. The sets of SHFS are interpreted in the light of sUuchlral changes between these phases. The EPR line features in the intermediate phase are analysed in the framework of a sWic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The modulational amplitude (∆ ) could be determined by the simulation of the spectra at = 135 using estimated from the simulation at = 90 . In our model, the rotational modulation of [Mg(H 2 O) 6 ] 2+ influenced on the spectra at = 135 not to produce the 'edge singularities' [19,20] but to reduce the linewidth. This effect can be explained as follows: The signal for the different orientation of [Mg(H 2 O) 6 ] 2+ arising from the rotational modulation is added in (8), and the linewidth and the intensity of the spectrum transformed from each signal can be distinct owing to the reorientation of [Mg(H 2 O) 6 ] 2+ .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The modulational amplitude (∆ ) could be determined by the simulation of the spectra at = 135 using estimated from the simulation at = 90 . In our model, the rotational modulation of [Mg(H 2 O) 6 ] 2+ influenced on the spectra at = 135 not to produce the 'edge singularities' [19,20] but to reduce the linewidth. This effect can be explained as follows: The signal for the different orientation of [Mg(H 2 O) 6 ] 2+ arising from the rotational modulation is added in (8), and the linewidth and the intensity of the spectrum transformed from each signal can be distinct owing to the reorientation of [Mg(H 2 O) 6 ] 2+ .…”
Section: Resultsmentioning
confidence: 97%
“…Three 2(∆ ) which can be attributed to three unequal water molecules in [Mg(H 2 O) 6 ] 2+ were observed for each rotation. It is found that the electric field gradient (EFG) tensors for two deuterons in a water molecule are averaged by the fast 180 flip of H 2 O resulting in the same tensors [9,12] and that inversion symmetry exists for [Mg(H 2 O) 6 ] 2+ at this temperature [2]. The fitting calculation for the rotation around the axis was performed with the equation [13] 2(∆ ) = 3 4 + ( ) cos (2 ) (1) + 2 sin (2 ) where is the angle between the axis and the external magnetic field 0 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations